Comparison of two recent ceramide-based coronary risk prediction scores: CERT and CERT-2. (25th November 2020) - Leiherer, A; Muendlein, A; Saely, C.H; Laaksonen, R; Laaperi, M; Vonbank, A; Fraunberger, P; Drexel, H
Abstract:  : The Coronary Event Risk Test (CERT) is a validated cardiovascular risk predictor that uses circulating ceramide concentrations to allocate patients into one of four risk categories. This test has recently been updated (CERT-2), now additionally including phosphatidylcholine concentrations. The purpose of this study was to investigate the power of CERT and CERT-2 to predict cardiovascular mortality in patients with cardiovascular disease (CVD). We investigated a cohort of 999 patients with established CVD. Overall, comparing survival curves (figure) for over 12 years of follow up and the predictive power of survival models using net reclassification improvement (NRI), CERT-2 was the best predictor of cardiovascular mortality, surpassing CERT (NRI=0.456; p=0.01) and also the 2019 ESC-SCORE (NRI=0.163; p=0.04). Patients in the highest risk category of CERT as compared to the lowest category had a HR of 3.63 [2.09–6.30] for cardiovascular death; for CERT-2 the corresponding HR was 6.02 [2.47–14.64]. Among patients with T2DM (n=322), the HR for cardiovascular death was 3.00 [1.44–6.23] using CERT and 7.06 [1.64–30.50] using CERT-2; the corresponding HRs among non-diabetic subjects were 2.99 [1.20–7.46] and 3.43 [1.03–11.43], respectively. We conclude that both, CERT and CERT-2 scores are powerful predictors of cardiovascular mortality in CVD patients, especially in those patients with T2D. Performance is even higher with CERT-2. Funding Acknowledgement: Type of funding source: None